The ethics of speech and thought representation in literary journalism. (July 2014) - Mitchell, Philip
This article applies a discourse analytical approach to the reporting of speech and thought in order to explore the parameters of core ethical quandaries in literary journalism, focusing in particular on the reconstruction or re-imagining of dialogue and thought. It thus focuses on the journalists' duties, firstly, towards their sources (specifically, to both the propositional content and the verbatim words of their subjects' truth claims), and, secondly, their perceived obligations towards their readers (regarding narrative accessibility, drama, resolution and lucidity). It then proceeds to discuss recent book-length examples of literary journalism from Spain and France. The article's central claim is that an alternative approach to such issues is identifiable in Spanish journalist Javier Cercas's work, in particular in his widely acclaimed re-exploration (2009) of the attempted coup d'etat in Madrid in 1981. Cercas's text, like many notable examples of literary journalism, is informed by a comprehensive set of interviews and by exhaustive archival research. Cercas goes further, however, in the thoroughness and rigour of the attribution of his reconstructions of speech and thought. The book incorporates, moreover, many explicit or implicit markers of a reported idea's dubitative or tentative status, a concern which continually shapes the text's overall representational choices, and which can be seen as a timely response to calls for writers working within a literary journalism tradition to develop a form of implicit ethical contract with their readers.